2010
DOI: 10.1042/bj20100414
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes and alteration ofFbn1andCol3A1gene expression under hyperglycaemic and hyperinsulinaemic conditions

Abstract: Little is known regarding the role of hyperglycaemia on histone H3 modifications and, in turn, altering the expression of genes during the development of diabetes-associated complications. In the present study, we have investigated the hyperinsulinaemia/hyperglycaemia-induced epigenetic changes and alteration of Fbn1 (fibrillin 1) and Col3A1 (collagen type III α1) gene expression. Insulin resistance and Type 2 diabetes in male Sprague-Dawley rats was developed by feeding rats an HFD (high-fat diet) and adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 38 publications
3
55
0
1
Order By: Relevance
“…These prospective findings also support the notion that ethnicity-specific susceptibility genes and process are involved in the complex pathogenesis of CVD and T2D. 26 …”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These prospective findings also support the notion that ethnicity-specific susceptibility genes and process are involved in the complex pathogenesis of CVD and T2D. 26 …”
Section: Discussionsupporting
confidence: 73%
“…Forty-five of these genes have been implicated previously in CVD (24 genes) [24][25][26] and T2D (21 genes).…”
Section: Identification Of Biological Pathways Using Integrative Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports showed that kidneys from diabetic animals exhibit changes in global histone PTMs as well as H3KAc at the fibrillin 1 promoter and that HDAC-2 may mediate ECM accumulation and epithelial-to-mesenchymal transition in the diabetic kidney and in TGF-␤1-treated epithelial cells (14,37). We recently demonstrated that TGF-␤1-induced profibrotic gene expression in MCs was associated with specific alterations in the levels of key active and repressive histone lysine methylation marks at their promoters (51).…”
Section: ␤1mentioning
confidence: 99%
“…HDAC2, 4 and 5 were upregulated in streptozotocin-induced diabetic nephropathy, db/db mouse models, and diabetic patient kidney biopsies [20,21]. HDAC-2 mediated extracellular matrix accumulation and epithelial-to-mesenchymal transition in the diabetic kidney and in TGF-β1-treated epithelial cells [22,23]. HDAC inhibitors, including Trichostatin A (TSA), have been reported to attenuate diabetic nephropathy [24][25][26].…”
Section: Discussionmentioning
confidence: 99%